Abbreviated New Drug Applications: Generic Drug User Fee Amendments Act Analysis of Application Quality Metrics. (September 2019) - Woo, Jason; Luan, Jingyu (Julia); Li, Zili; Grosser, Stella; Peters, John; Chazin, Howard
Implementation of the first Generic Drug User Fee Amendments of 2012 (GDUFA I) provided funding to the US Food and Drug Administration (FDA) for modernizing review of the FDA/CDER Generic Drug Program. Under GDUFA I, FDA agreed to reduce the backlog of pending generic Abbreviated New Drug Applications (ANDAs), improve the efficiency of generic drug review, and reduce the number of review cycles with the goal of reducing overall time to approval. This study presents a preliminary analysis of initial filing and regulatory first actions on ANDAs during GDUFA I cohort year 3 (CY3) and cohort year 4 (CY4). It highlights initial successes and areas of improvement in the ANDA review process for both FDA and ANDA applicants to improve the efficiency of providing the public with high-quality, affordable generic drugs.